Thioredoxin-1 Protects Spinal Cord from Demyelination Induced by Methamphetamine through Suppressing Endoplasmic Reticulum Stress and Inflammation - Yang, Lihua; Guo, Yinli; Huang, Mengbin; Wu, Xiaoli; Li, Xiang; Chen, Guobing; Li, Ye; Bai, Jie (Frontiers in Neurology, 2018)
Methamphetamine (METH) is a psychostimulant abused around the world. Emerging evidence indicates that METH causes brain damage. However there are very few reports on METH-induced demyelination. Thioredoxin-1 (Trx-1) is a redox regulating protein and plays the roles in protecting neurons from various stresses. However, whether Trx-1 resists demyelination induced by METH has not been reported. In present study we found that METH induced thin myelin sheaths, whereas Trx-1 overexpression transgenic (TG) mice restored the myelin sheaths thickness. The expressions of myelin-associated glycoprotein (MAG), myelin basic protein (MBP) and Cyclin-dependent kinase 5 (CDK5) were decreased by METH, whereas, these alterations were blocked in Trx-1 TG mice. The expressions of procaspase-12 and procaspase-3 were decreased by METH, the expression of calpain1 was increased by METH, whereas the alterations were suppressed in Trx-1 overexpression TG mice. As same as, the expressions of the extracellular signal-regulated kinase (ERK), nuclear factor κB (NF-κB), tumor necrosis factor-alpha (TNF-α) and interleukin-1beta (IL-1β) were induced by METH, which were suppressed in Trx-1 TG mice. These data suggest that Trx-1 may play a critical role in resisting the METH-mediated demyelination in spinal cord through regulating ER stress and inflammation pathways.